The Sentence Reconstruction Media to Improve Student's Understanding of Jumlah Fi'liyah at MA Unggulan Amanatul Ummah Surabaya - Fauziah, Mia Artanti; Syafi'i (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2026)
Mastery of Arabic verbal sentence structure (jumlah fi’liyah) is fundamental to grammatical competence, yet many Grade X students struggle to grasp the syntactic relationships among fi’il, fa’il, and maf’ul bih. Research gap: prior studies on interactive media in Arabic learning rarely focused specifically on sentence reconstruction for jumlah fi’liyah at the senior Islamic high school (MA) level. Novelty: this study specifically investigates sentence reconstruction media targeting jumlah fi’liyah mastery in an MA context. This study aims to evaluate the effectiveness of such media in enhancing students’ ability to identify and reconstruct verbal sentence components. Using a quantitative one-group pretest–posttest design, 15 Grade X students at MA Unggulan Amanatul Ummah Surabaya participated. Data were collected via expert-validated objective tests and analyzed using descriptive statistics, normality testing, and paired sample t-test (SPSS). Results show a significant score improvement from a mean of 64.13 to 87.06 (p = 0.000). Main contribution: this study provides empirical evidence that reconstruction-based learning effectively strengthens Arabic grammar instruction and offers pedagogical implications for future MA-level curriculum development.